CAIMAN CF. LATIROSTRIS (ALLIGATORIDAE, CAIMANINAE) IN THE LATE MIOCENE PALO PINTADO FORMATION, SALTA PROVINCE, ARGENTINA: PALEOGEOGRAPHIC AND PALEOENVIRONMENTAL CONSIDERATIONS (Ameghiniana, 2013)
The three recognized species of Caiman –C. latirostris, C. yacare and C. crocodilus– currently live in northern and central South America. Except for the fragmentary dentary of a putative Caiman from Oligocene rocks in Brazil, the genus has been reliably recorded in rocks of ages spanning the Neogene, when species of Caiman were a constant component of the South American crocodyliofauna. The major taxonomical diversification of Caiman occurred during the late Miocene, which is well documented in the area of Paraná (northeastern Ar- gentina). Fossil crocodylians in Paraná are represented by one gavialid and caimanines, with at least five species of Caiman (including C. la- tirostris). This assemblage represents the southernmost record of Crocodylia living in "Amazonia" during the Miocene. In this work we confirm the record of Miocene caimans outside the Paraná and we prove the presence of Caiman cf. latirostris in present-day northwestern Argentina during the late Miocene. The taxonomic identification is based on a fragment of a left mandible with the same ornamentation, outline and dentition as Caiman, and with a symphyseal morphology similar to that of Caiman latirostris. The material comes from the upper part of the Palo Pintado Formation in the southern region of Valle Calchaquí (Salta Province). This unit was deposited in a sand-gravel flu- vial system with associated ponds between 10.29 ±0.11 Ma (K/Ar) and 5.27 ±0.28 Ma (206Pb/238U).